2016
DOI: 10.1098/rsbl.2016.0258
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B radiation alters movement and thermal selection of zebrafish ( Danio rerio )

Abstract: Temperature and ultraviolet B (UV-B) interact in causing cellular damage and impairing locomotor performance. Here, we test the hypothesis that movement and thermal selection of zebrafish (Danio rerio) change in the presence of UV-B, and in particular, that fish which were chronically exposed to UV-B avoid high and low temperature extremes to maximize activities of antioxidant enzymes. Fish chronically (two to three weeks) exposed to UV-B had increased reactive oxygen species (ROS)-induced damage to proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Nevertheless, zebrafish showed reduced swimming performance when exposed to UVB for two weeks (3.3 W m -2 , 1.19 kJ m -2 d -1 ). This reduction in muscular activity can be part of a mechanism to minimize intrinsic reactive oxygen species (ROS) production after exposure to UVB (Seebacher et al 2016). The predatory performance of the reef fish Patagonothen cornucla, a species inhabiting the intertidal areas of the Patagonian coast, was affected after UVB exposure (Valinas and Helbling 2016).…”
Section: Juveniles and Adultsmentioning
confidence: 99%
“…Nevertheless, zebrafish showed reduced swimming performance when exposed to UVB for two weeks (3.3 W m -2 , 1.19 kJ m -2 d -1 ). This reduction in muscular activity can be part of a mechanism to minimize intrinsic reactive oxygen species (ROS) production after exposure to UVB (Seebacher et al 2016). The predatory performance of the reef fish Patagonothen cornucla, a species inhabiting the intertidal areas of the Patagonian coast, was affected after UVB exposure (Valinas and Helbling 2016).…”
Section: Juveniles and Adultsmentioning
confidence: 99%
“…Even though studies demonstrating an interaction of ROS production and behaviour in zebrafish larvae are lacking in the literature, at later developmental stages in zebrafish, an interaction of ROS production and movement was observed after chronic 3-hour daily exposure to UVB radiation (Seebacher et al, 2016). In this study, the ROS formation was significantly decreased in the 37.4 J/cm 2 UVA dose at 72 hpf.…”
Section: Behaviourmentioning
confidence: 43%
“…Independent of the aforementioned effects of UVB exposition on body size and possibly related behavioural responses, an enhanced formation of ROS may be responsible for the behavioural changes in UVB enhanced -fish. Seebacher et al [7] found an increase in ROS-induced damage in UVB-exposed zebrafish (Danio rerio) together with a reduced swimming performance at high temperatures compared with fish from a control group. By contrast, activity levels were not different between treatment groups in the present study so that comparable ROS-mediated effects on swimming performance can largely be ruled out.…”
Section: Discussionmentioning
confidence: 99%